2011
DOI: 10.1080/1550428x.2011.537231
|View full text |Cite
|
Sign up to set email alerts
|

Hearing the Voices of Lesbian Women Having Children

Abstract: This is an electronic version of an article published in Journal of GLBT Family Studies, 7[1/2], 2011. Journal of GLBT Family Studies is available online at: http://www.informaworld.com/smpp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
1
12
0
4
Order By: Relevance
“…Almost all the mothers talked about their child's future and were worried about how their two‐mother family structure could affect their child. This concern for the child, who has to live with its mothers’ choice, was also expressed by lesbian mothers in the USA (Wall, ). Some mothers in this study hoped that their child would be a mentally strong person and some feared their child would face difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the mothers talked about their child's future and were worried about how their two‐mother family structure could affect their child. This concern for the child, who has to live with its mothers’ choice, was also expressed by lesbian mothers in the USA (Wall, ). Some mothers in this study hoped that their child would be a mentally strong person and some feared their child would face difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this suggests that not all LGBQ people have complete or accurate knowledge about the law, a finding corroborated by Baumle and Compton (2011) and Kazyak (2015). Similarly, Wall (2011) surveyed 479 sexual minority women about their decisions about whether or not to become a parent. She analyzed people's responses to an open-ended question that asked what the most difficult thing is when deciding about whether not to become a mother.…”
Section: Desiring Parenthoodmentioning
confidence: 91%
“…There's, you know, Massachusetts, New York, and California" (p. 376). Other work underscores the finding that legal barriers can negatively impact LGBQ people's perceptions about their ability to become a parent (Brown, Smalling, Groza, & Ryan, 2009;Riskind, Patterson, & Nosek, 2013;Wall, 2011). For instance, based on analysis of survey data from 1,098 gays and lesbians without children, Riskind et al (2013) found that those living in favorable social and legal climates believed they could become parents while those in unfavorable social and legal climates were more likely to report doubts as to whether they could become parents.…”
Section: Social Barriersmentioning
confidence: 99%